BSR versus Climate Change and Slides - Tinivella, U.; Giustiniani, M.; Accettella, D. (Journal of Geological Research, 2011)
We investigate the relationship between climate change and hydrate stability in two peri-Antarctic areas: Antarctic Peninsula and South Chile. We consider these areas because the polar and subpolar areas are the most sensitive about global change. The zone, where the methane can be easily released by hydrate melting, is the shallow water, that is, in proximity of the intersection between the BSR and the sea bottom. In order to simulate the effect of climate change on hydrate stability, we consider the following seven scenarios for both areas: present environmental condition; sea bottom temperature increase/decrease of water depth increase/decrease of 100 m; sea bottom temperature and water depth increase/decrease of and 100 m, respectively. On the basis of our result, we can draw the conclusion that the modeling is a useful tool to understand the effect of the climate change on hydrate stability. Moreover, in these areas where the sea bottom temperature is influenced by temperature increase, slides could be easily triggered by hydrate dissociation.